(1,2)*-D ?-Closed Sets in Bitopological Spaces - A. Saranya, O. Ravi (Mathematical Statistician and Engineering Applications, 2021)
In the paper, we introduce the notions of (1,2)*- -closed sets and (1,2)*-D-closed sets in bitopological spaces.